2014
DOI: 10.3390/ijerph110504652
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Positive Psychology Using Social Networking Sites: A Study of New College Entrants on Facebook

Abstract: This study explores the potential of promoting college students’ positive psychological development using popular online social networks. Online social networks have dramatically changed the ways college students manage their social relationships. Social network activities, such as checking Facebook posts dominates students’ Internet time and has the potential to assist students’ positive development. Positive psychology is a scientific study of how ordinary individuals can apply their strength effectively whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 7 publications
2
15
0
Order By: Relevance
“…Even though Baym et al (2004) discovered that students prefer to communicate faceto-face, findings of this research concur with those of Chen and Hanasono (2016) who established that distance and cost barriers in international communications necessitate the utilisation of SNSs like Facebook as these are cheap and more convenient to the students than the traditional means of communication such as voice calls. These results were similar to those of a previous study conducted on a sample of 142 Chinese international students in Japan which indicated that the need to stay connected positively influences Facebook usage (Chang et al 2014). …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Even though Baym et al (2004) discovered that students prefer to communicate faceto-face, findings of this research concur with those of Chen and Hanasono (2016) who established that distance and cost barriers in international communications necessitate the utilisation of SNSs like Facebook as these are cheap and more convenient to the students than the traditional means of communication such as voice calls. These results were similar to those of a previous study conducted on a sample of 142 Chinese international students in Japan which indicated that the need to stay connected positively influences Facebook usage (Chang et al 2014). …”
Section: Discussionsupporting
confidence: 90%
“…According to Schneider et al (2016), SNS users use them to stay connected with close people who would not be physically present, mainly to ensure that they are not left behind and also because of the need to belong. In the same line, a recent study on a sample of 142 Chinese international students in Japan indicated that people use SNSs to stay connected as they benefit from increased social networking and psychological well-being (Chang et al 2014). International students use SNSs to connect and stay connected with their families and former classmates from their countries of origin (Forbush & Foucault-Welles 2016).…”
Section: The Need To Connectmentioning
confidence: 96%
See 2 more Smart Citations
“…College students are willing to accept the more creative and fresh health education method. The present study has concluded that seminars or lectures are acceptable by majority of the students, the students' associations play a positive role in health education and with the development of network, social network has become one of the most popular informal channels for students [22], but key figures considered network publicity of health knowledge were imperfect, so that school may consider using its potential social influence to assist students in their life adjustments and positive development in physical and psychological health [23,24]. Our results found that the sports facilities and venues don't fully meet the need of most students.…”
Section: Discussionmentioning
confidence: 99%